Fertility loss: negative effects of environmental toxicants on oogenesis - Yao, Xiaoxi; Liu, Weijing; Xie, Yidong; Xi, Mingrong; Xiao, Li (Frontiers in Physiology, 2023)
There has been a global decline in fertility rates, with ovulatory disorders emerging as the leading cause, contributing to a global lifetime infertility prevalence of 17.5%. Formation of the primordial follicle pool during early and further development of oocytes after puberty is crucial in determining female fertility and reproductive quality. However, the increasing exposure to environmental toxins (through occupational exposure and ubiquitous chemicals) in daily life is a growing concern; these toxins have been identified as significant risk factors for oogenesis in women. In light of this concern, this review aims to enhance our understanding of female reproductive system diseases and their implications. Specifically, we summarized and categorized the environmental toxins that can affect oogenesis. Here, we provide an overview of oogenesis, highlighting specific stages that may be susceptible to the influence of environmental toxins. Furthermore, we discuss the genetic and molecular mechanisms by which various environmental toxins, including metals, cigarette smoke, and agricultural and industrial toxins, affect female oogenesis. Raising awareness about the potential risks associated with toxin exposure is crucial. However, further research is needed to fully comprehend the mechanisms underlying these effects, including the identification of biomarkers to assess exposure levels and predict reproductive outcomes. By providing a comprehensive overview, this review aims to contribute to a better understanding of the impact of environmental toxins on female oogenesis and guide future research in this field.